Supplement to the Revised Statutes of the State of Wisconsin, 1878, Containing the General Laws from 1879 to 1883, with the Revisers’ Notes to the Statutes of 1878 and Notes to Cases Construing and Applying These and Similar Statutes by the Supreme Court of Wisconsin and the Courts of Other States, at 847, ch. 181, §4397a(1) (1883) - (:unkn) unknown (General Publisher, 1882)
It shall be unlawful for any person to sell or use, or have in his possession, for the purpose of exposing for sale or use, any toy pistol, toy revolver, or other toy fire-arm.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES